Calculating the Social Return on Investment of a Japanese Professional Soccer Team's Corporate Social Responsibility Activities - Oshimi, Daichi; Yamaguchi, Shiro; Fukuhara, Takayuki; Tagami, Yoshifumi (Frontiers in Sports and Active Living, 2022)
In response to the lack of evidence for visualizing the monetary value of professional sport teams' CSR-related social impact, this study aimed to calculate the social impact of a Japanese professional soccer team's corporate social responsibility (CSR) activity (i.e., community soccer/physical activity program) by using a social return on investment (SROI) framework. Specifically, Matsumoto Yamaga Football Club was used for the estimation. This professional soccer team was ranked in the top division of the league (J1) during the estimation period and engaged in CSR activities at 129 community soccer schools in a year (2019–2020). The SROI calculation involved five stages: (1) identifying key stakeholders, (2) mapping inputs, outputs, and outcomes, (3) measuring and valuing outcomes, (4) establishing impact, and (5) calculating SROI. For the first step, we specified seven major stakeholders (soccer team, nursery school children, parents, coaches, teachers, local governments, and local football associations) and conducted interview investigations with each stakeholder. Our result showed that the social value of the teams' targeted community soccer school was USD 54,160, and the total financial and non-financial inputs to the school were USD 10,134, meaning an SROI ratio of 5.3. This means that for every USD invested in a community soccer school, social benefit worth USD 5.3 was generated. This study contributes to advancing social impact research in sport by shedding light on the monetary value of the social impact of professional sport teams' CSR activities. In addition, it also has practical implications for team managers looking to utilize CSR activities as a management strategy, through cost-effective investment and optimization of resources.